Look what came from Mexico - Harvey(3, (BMiless (New York F. Watts, 1998)
Describes some familiar foods, arts and crafts, music, sports, holidays, and more that originated in Mexico
Hurg
5
Keywords: Civilization -- Mexican influences -- Juvenile literature; Mexico -- Civilization -- Juvenile literature